Relationship between endoscopic mucosal healing and histologic inflammation during remission maintenance phase in ulcerative colitis: a retrospective study - Kanazawa, Mimari; Takahashi, Fumiaki; Tominaga, Keiichi; Abe, Keiichiro; Izawa, Naoya; Fukushi, Koh; Nagashima, Kazunori; Kanamori, Akira; Takenaka, Kazuhiro; Sugaya, Takeshi; Iijima, Makoto; Takada, Atsuko; Imai, Yasuo; Hiraishi, Hideyuki; Irisawa, Atsushi (Endoscopy International Open, 2019)
Background and study aims Recently, histological inflammation has been suggested to be an important predictor of sustained remission or relapse of ulcerative colitis (UC). In this study, we retrospectively compared severity of histological inflammation with endoscopic findings in UC patients with mucosal healing (MH) in the remission maintenance phase, and investigated whether histological healing could be a predictor of sustained remission.Patients and methods This study included 166 patients with MH in the remission maintenance phase. Endoscopic evaluation was based on the Mayo endoscopic subscore (MES), and MH was defined as MES 0 or 1. Severity of histological inflammation was graded according to the Matts classification. Patients with Matts 1 and 2 were included in the histological healing (HH) group, and those with Matts 3, 4, and 5, in the non-histological healing (NHH) group. In patients with MH, incidence of relapse was compared and analyzed according to severity of histological inflammation.Results The remission maintenance rate was significantly higher in the MES 0 group than in the MES 1 group (P = 0.004). The rate was significantly higher in the HH group than in the NHH group (P = 0.003). Within the MES 1 group, the rate was significantly higher in the HH subgroup than in the NHH subgroup (P = 0.030).Conclusions This retrospective study suggests that histological healing can be a predictor of sustained remission in UC patients, and examination of histological inflammation provides useful information for long-term management of UC, particularly in patients with MES 1.